Study of Polymer Layer Characteristics on Al and Ti Alloys (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, the mechanical properties of organic coatings based on epoxy resin (DGEBA DER 332) and two diamines comonomers (IPD and 3DCM) were investigated. The coatings were applied to substrates made of aluminum and titanium alloys. Differential scanning calorimetry and infrared spectroscopy were used to study the effect of the coating thickness on the degree of reaction of the substrate of both alloys and compare with the volumetric values. The residual stress and Young's modulus of the coatings were calculated using one-dimensional analysis based on beam theory with the introduction of a biaxial modulus for isotropic stress (thin plate theory). A stiffness factor was introduced, since deformations in the coating lead to deformations in the substrate. During the thermal cure cycle, a loss of curing agent was observed and thus a change in the degree of reaction of the coating.